Pregnancy loss: Consequences for mental health - Cuenca, Diana (Frontiers in Global Women's Health, 2023)
Pregnancy loss, in all its forms (miscarriage, abortion and fetal loss) is one of the most frequent adverts pregnancy outcome, despite of this, the psychological impact of this losses is usually underestimated. Although the individual response to this adverse outcome could be different between women, and could be influence by age, race, culture or religious beliefs, most of them feel anxiety, stress and depression symptoms. Health providers are used to deal with this diagnosis due to its high frequency. However the correct management of the process of diagnosis, information and treatment of a pregnancy loss can greatly decrease the adverse mental consequences of these women and couples involved. The aim of this review is to know the different types of pregnancy loss and how each one influence in the mental health of women affected and partners; in short and long time; review the risk factors and protective ones in order to identify women at risk of mental health consequences; and finally give some advice for the health providers to help this women and partners to cope with pregnancy loss. Finally we give some points for health providers to follow up in order to management a pregnancy loss that are common for spontaneous, induced, recurrent miscarriage or stillbirth.